Sistem Pendidikan di Korea Selatan : Struktur, Tahapan Pendidikan, Kurikulum, Perbandingan Pendidikan, Inovasi dan Tantangan - Yusra Ramadhana; Mislaini Mislaini; Sri Gina Miranti (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2025)
The South Korean education system is renowned for its structured organization and focus on high academic achievement. Its curriculum incorporates modern technology to enhance the learning experience, but high academic pressure poses significant challenges, particularly concerning students’ mental well-being. Compared to Indonesia, which adopts a more holistic approach through the Merdeka Curriculum, South Korea excels in producing globally competitive students. This article explores the comparison of the two education systems, highlighting innovations, challenges, and reforms needed to create inclusive and sustainable education.